2014
DOI: 10.1186/2051-5960-2-39
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH ligands JAG1 and JAG2 as critical pro-survival factors in childhood medulloblastoma

Abstract: Medulloblastoma (MB), the most common pediatric malignant brain cancer, typically arises as pathological result of deregulated developmental pathways, including the NOTCH signaling cascade. Unlike the evidence supporting a role for NOTCH receptors in MB development, the pathological functions of NOTCH ligands remain largely unexplored. By examining the expression in large cohorts of MB primary tumors, and in established in vitro MB models, this research study demonstrates that MB cells bear abnormal levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 46 publications
(82 reference statements)
1
27
0
1
Order By: Relevance
“…It has been demonstrated that JAG1 is overexpressed in various types of cancer, and it is involved in several aspects of tumor biology, including cell growth, apoptosis, cancer stem cell maintenance, epithelial-mesenchymal transition and metastasis (38). Fiaschetti et al (39) revealed that JAG1 is overexpressed in the majority of medulloblastoma (MB), and JAG1 is crucial in maintaining Notch-related pro-survival functions in MB cells (39). In the present study, JAG1 expression was demonstrated to be regulated by miR-140-5p in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that JAG1 is overexpressed in various types of cancer, and it is involved in several aspects of tumor biology, including cell growth, apoptosis, cancer stem cell maintenance, epithelial-mesenchymal transition and metastasis (38). Fiaschetti et al (39) revealed that JAG1 is overexpressed in the majority of medulloblastoma (MB), and JAG1 is crucial in maintaining Notch-related pro-survival functions in MB cells (39). In the present study, JAG1 expression was demonstrated to be regulated by miR-140-5p in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…All data used are accessible through the open access platform R2 for visualization and analysis of the microarray data ( http://r2.amc.nl ). The following datasets were used: Delattre 54 MAS 5.0 – u133p2 (54 MB samples), Gilbertson 76 MAS 5.0 – u133p2 (76 pediatric MB samples, PubMed link: 22722829), Kool 62 MAS 5.0 – u133p2 (62 human MB samples, PubMed link 18769486), Northcott 103 rma_sketch – huex10t (103 primary MB samples, PubMed link 20823417) and MAGIC 285 rma-sketch – hugene11t (285 primary MB samples, PubMed link 22832581) Analysis was performed as described in (Fiaschetti et al 2014 ). The nine normal cerebellum samples are from human subject aged as follows: Donor 1–25 year old male; donor 2–38 year old male; donor 3–39 year old female; donor 4–30 year old male; donor 5–35 year old male; donor 6–52 year old male; donor 7–50 year old female; donor 8–48 year old female; donor 9–53 year old female; donor 10–23 year old female.…”
Section: Methodsmentioning
confidence: 99%
“…HD-MBO3 [17] was generously provided by Till Milde (DKFZ, Germany). DAOY cells were cultured as described in [33]. DAOY Lifeact-enhanced green fluorescent protein LA-EGFP cells were produced by lentiviral transduction of DAOY cells with pLenti-LA-EGFP.…”
Section: Cells and Cell Culturementioning
confidence: 99%